2017
DOI: 10.1111/ajr.12346
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ knowledge of Q fever and prevention approaches in New South Wales

Abstract: Strengthening existing GP knowledge and services leading to expanded provision of screening/vaccination could improve the coverage of Q fever vaccine in endemic NSW farming and rural communities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 10 publications
4
18
1
Order By: Relevance
“…Currently, the Australian Immunisation Handbook recommends QFV for wildlife and zoo workers who have contact with at-risk animals, including kangaroos and bandicoots [ 8 ], however only 8.1% (13/160) AWRs in this study had undergone vaccination. This is consistent with other Australian studies which have also reported low levels of vaccine uptake in groups for whom vaccination is recommended [ 30 , 38 , 43 , 60 ], Similarly, this handbook recommends QFV for veterinary nurses, but alarmingly 93.3% (24/26) of the veterinary nurses participating in this study were not vaccinated. Furthermore, evidence of C. burnetii antibody was observed in two of the 24 (8.3%) unvaccinated veterinary nurses ( Table 2 ) indicating exposure to C. burnetii and reinforcing the need for QFV amongst this group.…”
Section: Discussionsupporting
confidence: 91%
“…Currently, the Australian Immunisation Handbook recommends QFV for wildlife and zoo workers who have contact with at-risk animals, including kangaroos and bandicoots [ 8 ], however only 8.1% (13/160) AWRs in this study had undergone vaccination. This is consistent with other Australian studies which have also reported low levels of vaccine uptake in groups for whom vaccination is recommended [ 30 , 38 , 43 , 60 ], Similarly, this handbook recommends QFV for veterinary nurses, but alarmingly 93.3% (24/26) of the veterinary nurses participating in this study were not vaccinated. Furthermore, evidence of C. burnetii antibody was observed in two of the 24 (8.3%) unvaccinated veterinary nurses ( Table 2 ) indicating exposure to C. burnetii and reinforcing the need for QFV amongst this group.…”
Section: Discussionsupporting
confidence: 91%
“…As reported in other Australian studies, 5,21,22 we found that only 40% of people in groups for whom vaccination is recommended knew about the Q fever vaccine and only 10% had been vaccinated; even among those who knew about the vaccine, only 26% had been vaccinated. Targeted awareness campaigns (as currently underway in NSW) 23 are needed, especially as the main reported reason for not being vaccinated was the perceived lack of risk.…”
Section: Discussionsupporting
confidence: 83%
“…Targeted awareness campaigns (as currently underway in NSW) are needed, especially as the main reported reason for not being vaccinated was the perceived lack of risk . However, access to the vaccine can also be a problem . A new online training module for rural general practitioners should improve access and increase the number of early Q fever diagnoses, which may reduce the risk of chronic infection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Issues affecting vaccine uptake have been reviewed for farmers, veterinarians and veterinary assistants. 29 Awareness and risk appreciation are often poorly understood by the individual and GP. Additionally, cost and inconvenience to the patient and GP are also factors influencing the uptake of vaccines.…”
Section: Vaccinationmentioning
confidence: 99%